Bisphosphonate-associated jaw osteonecrosis in the treatment of rheumatoid arthritis - Gabriela Dias Rosso dos Santos; Luciana Corrêa; Danielle Lima Corrêa de Carvalho (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT This literature review aimed to raise the relationship between rheumatoid arthritis and mandibular osteonecrosis associated with bisphosphonates. The articles were collected in Pubmed, Bireme, Cochrane and Scielo between the years 2000 and 2023, the articles that contained hypotheses of correlation with the theme or that contained case reports (inclusion of publications between 2005 and 2019) where osteonecrosis appeared during treatment for rheumatoid arthritis were included. The survey allowed an assessment of the profile of the patient with rheumatoid arthritis, as well as the bone consequences of the use of oral methotrexate and bisphosphonates and treatment options; as well as the success of conservative and surgical techniques against mandibular osteonecrosis. Although the relationship between mandibular osteonecrosis and rheumatoid arthritis is not completely understood, we can conclude that the dental surgeon and the rheumatologist must always be in communication in order to treat mandibular osteonecrosis in the best possible way, as well as prevent its onset.